Evaluation of the Biomarkers HMGB1 and IL-6 as Predictors of Mortality in Cirrhotic Patients with Acute Kidney Injury - Célio Geraldo de Oliveira Gomes; Marcus Vinicius Melo de Andrade; Ludmila Resende Guedes; Henrique Carvalho Rocha; Roberto Gardone Guimarães; Fernando Antônio Castro Carvalho; Eduardo Garcia Vilela (Mediators of Inflammation)
Background. Acute kidney injury (AKI) affects from 20% to 50% of cirrhotic patients, and the one-month mortality rate is 60%. The main cause of AKI is bacterial infection, which worsens circulatory dysfunction through the release of HMGB1 and IL-6. Objectives. To evaluate HMGB1 and IL-6 as biomarkers of morbidity/mortality. Methods. Prospective, observational study of 25 hospitalised cirrhotic patients with AKI. Clinical and laboratory data were collected at the time of diagnosis of AKI, including serum HMGB1 and IL-6. Results. The mean age was 55 years; 70% were male. Infections accounted for 13 cases. The 30-day and three-month mortality rates were 17.4% and 30.4%, respectively. HMGB1 levels were lower in survivors than in nonsurvivors at 30 days (1174.2 pg/mL versus 3338.5 pg/mL, p=0.035), but not at three months (1540 pg/mL versus 2352 pg/mL, p=0.243). Serum IL-6 levels were 43.3 pg/mL versus 153.3 pg/mL (p=0.061) at 30 days and 35.8 pg/mL versus 87.9 pg/mL (p=0.071) at three months, respectively. The area under the ROC curve for HMGB1 was 0.842 and 0.657, and that for IL-6 was 0.803 and 0.743 for discriminating nonsurvivors at 30 days and three months, respectively. In multivariate analysis, no biomarker was independently associated with mortality. Conclusion. HMGB1 levels were associated with decreased survival in cirrhotics. Larger studies are needed to confirm our results.